Development and kinematic analysis of a redundant, modular and backdrivable laparoscopic surgery robot - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, a redundant robotic forceps system with a modular architecture for minimally invasive surgery (MIS) is presented. The system consists of two parts: a 7 degrees of freedom (DOF) industrial robot acting as an external Remote Center of Motion (RCM or RCoM) mechanism that controls the Cartesian position of an instrument wrist with spherical motion at the incision-trocar entry point, and an attached novel back-drivable parallel wrist mechanism that can add intra-corporeal degrees of freedom. The wrist mechanism has 4-DOF and is able to perform 90-degree pitch, yaw, thrust and gripping motions. A closed form kinematic solution is also provided for the combined robotic system. The proposed design and solutions are validated with experiments on an actual prototype. Experiment results show that an operator can unilaterally control the motion of the forceps, through a haptic interface, as desired. © 2018 IEEE.